2x+1-3x-3+x=10-2x

Simple and best practice solution for 2x+1-3x-3+x=10-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+1-3x-3+x=10-2x equation:


Simplifying
2x + 1 + -3x + -3 + x = 10 + -2x

Reorder the terms:
1 + -3 + 2x + -3x + x = 10 + -2x

Combine like terms: 1 + -3 = -2
-2 + 2x + -3x + x = 10 + -2x

Combine like terms: 2x + -3x = -1x
-2 + -1x + x = 10 + -2x

Combine like terms: -1x + x = 0
-2 + 0 = 10 + -2x
-2 = 10 + -2x

Solving
-2 = 10 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-2 + 2x = 10 + -2x + 2x

Combine like terms: -2x + 2x = 0
-2 + 2x = 10 + 0
-2 + 2x = 10

Add '2' to each side of the equation.
-2 + 2 + 2x = 10 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = 10 + 2
2x = 10 + 2

Combine like terms: 10 + 2 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| 6(x+4)=7x-8 | | x+4/x+7=x-5/x-3 | | 7y+3y=9y+3 | | x/3+2y=5 | | n-10=18 | | 6x+16=9x+10 | | sqrt(5y+9)=7 | | 25=5/6w | | -4(8p-7)-p=106 | | r-9.1=-9.8 | | w+(-2)=-18forw | | 238=7(7b-1) | | -138=6(4n-3) | | n+8=n+2 | | 14+4n=8n-3(n-6) | | 5(5+2x)=105 | | 3x-y=37 | | 3ln(x-1)=15 | | 0.10x+0.10y=100 | | 1/6(x+4)=3x-4(2-x)-5 | | -114=6(-4+2a)+6a | | -9x-y=-59 | | 58-7x=11x+24 | | 2/5(2x+11)=3(4-3x)+12 | | 2/5x^2+1/5x-2=0 | | -6(1-6r)=138 | | 2/5(2x+11)=3(4x-3x)+12 | | -152=4(4k-6) | | -5n+18+3n=-6 | | n=2-3 | | -107=r+3(7r+1) | | 24x+19x= |

Equations solver categories